Development of an Augmented Reality-Based Biology E-Module Using a Deep Learning Approach to Improve High School Students’ Scientific Literacy - Ni Nyoman Serma Adi; Dewa Nyoman Oka; Ni Made Serma Wati; I Gusti Lanang Agung Parwata; I Gede Ratnaya; I Dewa Ayu Made Budhyani (At- Ta'lim : Jurnal Pendidikan, 2026)
This study aims to produce a biology e-module using Augmented Reality technology and a deep learning approach, and meets valid, practical, and effective standards in improving students' scientific literacy skills. The effectiveness test was conducted using a pre-experimental design one-group pretest-posttest design, and the results were analyzed using the N-Gain index. The process of creating the e-module follows a 4-D model consisting of four stages: define, design, development, and disseminate. However, this study only reached the development stage due to time constraints. The study shows that: (1) The development of the e-module obtained an average validity value of 3.4 based on the opinions of experts and practitioners, so it is considered valid; (2) the practicality aspect is met because the implementation of learning runs smoothly and the responses from teachers and students are in the very practical category; and (3) the e-module is proven to be effective in improving scientific literacy skills, as seen from the N-Gain value of 0.56 which is included in the moderate category. Thus, it can be concluded that the biology e-module based on Augmented Reality with a deep learning approach has met the criteria of being valid, practical, and effective, and is suitable for use as a learning medium to improve the scientific literacy of high school students.